2020
DOI: 10.1038/s41598-020-70765-w
|View full text |Cite
|
Sign up to set email alerts
|

C57BL/6J substrain differences in response to high-fat diet intervention

Abstract: C57BL/6J-related mouse strains are widely used animal models for diet-induced obesity (DIO). Multiple vendors breed C57BL/6J-related substrains which may introduce genetic drift and environmental confounders such as microbiome differences. To address potential vendor/substrain specific effects, we compared DIO of C57BL/6J-related substrains from three different vendors: C57BL/6J (Charles Rivers), C57BL/6JBomTac (Taconic Bioscience) and C57BL/6JRj (Janvier). After local acclimatization, DIO was induced by eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 46 publications
4
34
2
Order By: Relevance
“…Since C57BL/6 mouse strains are widely used in diet-induced obesity (DIO) studies, different substrains of C57BL/6 mice are also available. They include genetic and environmental differences such as those present in the microbiome [27] as well as differences in response to an HFD feeding [27][28][29][30]. A study carried out in C57BL/6JRj and C57BL/6NTac mice substrains, reported important differences in response to an HFD, and concluded that the C57BL/6JRj strain is protected against DIO regardless of physical activity and food intake [29].…”
Section: Animal Models Of Diet-induced Obesitymentioning
confidence: 99%
“…Since C57BL/6 mouse strains are widely used in diet-induced obesity (DIO) studies, different substrains of C57BL/6 mice are also available. They include genetic and environmental differences such as those present in the microbiome [27] as well as differences in response to an HFD feeding [27][28][29][30]. A study carried out in C57BL/6JRj and C57BL/6NTac mice substrains, reported important differences in response to an HFD, and concluded that the C57BL/6JRj strain is protected against DIO regardless of physical activity and food intake [29].…”
Section: Animal Models Of Diet-induced Obesitymentioning
confidence: 99%
“…Moreover, this difference may be explained by the fact that the C57Bl/6 mice used here do not have a mutation in the nicotinamide nucleotide transhydrogenase gene. It has been reported that C57Bl/6 J substrains that present this mutation display a higher susceptibility to gain fat mass and to an impairment of glucose tolerance induced by HFD in comparison to C57Bl/6 without the mutation 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Seven-week-old male C57BL/6J mice from the National Laboratory Animal Center (Taipei, Taiwan) were housed in a temperature-controlled (22 ± 2 °C) animal center with a 12:12 h light–dark cycle (light on at 07:00). C57BL/6J related mouse strains are widely used in diet-induced obesity animal models [ 18 ]. All animal experiments were approved by the Institutional Animal Care and Use Committee of Taipei Medical University (LAC-2020-0229) and performed in accordance with the NIH guide for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma lipids were extracted using the Folch method as previously described [ 18 ] with slight modifications. Briefly, 1.5 mL of methanol was added to a 40 µL plasma sample, followed by the addition of 3 mL of CHCl 3 and incubation for 1 h at room temperature with vortex mixing.…”
Section: Methodsmentioning
confidence: 99%